ANALISA KINERJA POMPA SENTRIFUGAL KAPAL KERUK - Christofel Jarot Yudaputranto (Asosiasi Dosen Muda Indonesia, 2024)
In general, a pump is a tool or machine that is used to move liquids from one place to another through a piping medium by adding energy to the fluid being moved and taking place continuously. Centrifugal force is the force that arises due to the movement of an object or particle through a curved (circular) path. Centrifugal force acts on the impeller to push the fluid to the outside so that the fluid velocity increases. In its application, a centrifugal pump is a pump that is very commonly used for pumping liquids in various industrial uses. One of them is a dredger used in the sludge dredging industry. From the pump data used, a study was carried out on the pumps used on the suction dredger to obtain pump power, head, capacity and energy efficient opportunities that can be achieved. From the results of the pump study, the following data were obtained: Efficiency (ɳ) : 70 %, Head (H) : 30 m, Capacity (Q) : 10300 ????3/ hour / 2,861 ????3/s, NPSH???? : 53.75 m, Pump power (P) : 5446.34 Kw